2021
DOI: 10.1089/lgbt.2020.0248
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sexual Orientation Acceptance with Reduced Suicide Attempts Among Lesbian, Gay, Bisexual, Transgender, Queer, and Questioning Youth

Abstract: Purpose: This study examined the relationship between sexual orientation acceptance from others and suicide attempts among lesbian, gay, bisexual, transgender, queer, and questioning (LGBTQ) youth. Methods: We analyzed data from a 2018 cross-sectional survey of LGBTQ youth between the ages of 13 and 24 years across the United States. Youth reported sexual orientation acceptance levels from parents, other relatives, school professionals, health care professionals, friends, and classmates to whom who they were '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…This current study is a pioneer cross-sectional study in France to analyze the role of parental and friend's support on suicide attempts among LGB adolescents. Suicide attempt remained associated with sexual orientation when considering possible related variables, which is consistent with previous studies (Green et al, 2021;Williams et al, 2021). A co-twin control study in youth males showed that suicide attempts remained signi cantly associated with same-gender sexual orientation after adjustment for substance abuse and depressive symptoms (Herrell et al, 1999).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This current study is a pioneer cross-sectional study in France to analyze the role of parental and friend's support on suicide attempts among LGB adolescents. Suicide attempt remained associated with sexual orientation when considering possible related variables, which is consistent with previous studies (Green et al, 2021;Williams et al, 2021). A co-twin control study in youth males showed that suicide attempts remained signi cantly associated with same-gender sexual orientation after adjustment for substance abuse and depressive symptoms (Herrell et al, 1999).…”
Section: Discussionsupporting
confidence: 86%
“…Faced with such a high proportion of suicide attempts among sexual minority adolescents, the identi cation of protective factors should be a focus. Previous studies reported that some protective factors have been identi ed and targeted in future interventions of suicide attempts such as family connectedness, acceptance of the mother, teacher caring, other adult caring, and school safety (Green et al, 2021;Johns et al, 2018;Padilla et al, 2010). Among these results, parental and friend's support are considered as the two most important protective factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social acceptance of MSM is variable across nations and cultures. [ 7 8 9 ] In America, social marketing has played a major role in social acceptance of gay, lesbian, bisexual and transgender people. Compared to a decade earlier, 60% of Americans are more likely to accept gay relationships and marriages.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Social and family acceptance and safe community environment have strong association with improved health conditions. [ 8 9 ] Fear of anticipated discrimination and disparity in access to health facilities is an universal phenomenon. [ 10 11 12 13 ] The ongoing COVID-19 pandemic has made the gender minority population more vulnerable.…”
Section: Introductionmentioning
confidence: 99%